Flap management of groin wounds following vascular procedures: A review of 270 flaps for vascular salvage. (March 2023) - Rajput, Sanjna; Kuruoglu, Doga; Salinas, Cristina A.; Sen, Indrani; Kalra, Manju; Moran, Steven L.
Summary: Background: Groin dehiscence following vascular procedures results in morbidity for patients with peripheral vascular disease. Controversy exists around the indications for flap coverage. We present an institutional experience with flap reconstruction of groin wounds after vascular procedures to identify predictors of beneficial outcomes. Patients and methods: A retrospective review of patients who had flap coverage for infected/nonhealing groin wounds following a vascular procedure between 1998 and 2021 was performed. Demographics and clinical characteristics, including flap and vascular graft type, were collected along with major complications. Univariate and multivariable logistic regression analyses were performed to assess the associations between procedures and major complications. Results: A total of 270 flaps were transferred to 237 patients. Thirty-three patients had bilateral wounds. The mean age and BMI were 67 ± 11 years and 27.9 ± 6.3 kg/m 2, respectively. Flaps included rectus femoris (n = 142), sartorius (n = 118), rectus abdominis (n = 7), and gracilis (n = 3). Covered vascular grafts included prosthetic materials (n = 200) and autografts (n = 70). The median length of hospital stay after surgery was 10 days (interquartile range=12), and the mean follow-up was 29.1 ± 39.2 months. The major complication rate was 38.5% with wound infection being the most common. Flaps successfully prevented the infection-related removal of the grafts in 98.9% of cases. Multivariable analysis revealed no significant associations between variables and having a major complication. Conclusions: Flap coverage of the inguinal vessels can be performed safely with favorable limb salvage. Wound complications were high, but graft salvage was excellent. Rectus femoris and sartorius muscle flaps were the most common flaps, yielding comparable outcomes.